3NaOH + H3PO4 -> Na3PO4 + 3H2O реакция обмена
SO3 + 2KOH -> K2SO4 + H2O реакция обмена
Cu(NO3)2 + Zn -> Zn(NO3)2 + Cu реакция замещения
H2SO4 +2 KOH -> K2SO4 + 2H2O реакция обмена
CaO + 2HCl -> CaCl2 + H2O реакция обмена
CO2 + Ca(OH)2 -> CaCO3 + H2O реакция обмена
3HCl + Al(OH)3 -> AlCl3 + 3H2O реакция обмена
Na2O + H2SO4 -> Na2SO4 + H2O реакция обмена
FeCl2 + 2KOH -> Fe(OH)2 + 2KCl реакция обмена
4Al + 3O2 -> 2Al2O3 реакция соединения
6HNO3 + Al2O3 -> 2Al(NO3)3 + 3H2O реакция обмена
Fe(OH)2 -> FeO + H2O реакция разложения
BaO + H2O -> Ba(OH)2 реакция соединения
SO3 + H2O -> H2SO4 реакция соединения
2AgNO3 + BaCl2 -> Ba(NO3)2 + 2AgCl реакция обмена
H2SO4 + Zn -> ZnSO4 + H2 реакция замещения
SO2 + K2O -> K2SO3 реакция соединения
2HCl + Mg -> MgCl2 + H2 реакция замещения
2Na + Cl2 -> 2NaCl реакция соединения
6NaOH + P2O5 -> 2Na3PO4 + 3H2O реакция обмена
Li2O + H2O -> 2LiOH реакция соединения
AgNO3 + HCl -> AgCl + HNO3 реакция обмена
2NH4Cl + Ca(OH)2 -> CaCl2 + 2NH3 + 2H2O реакция обмена
CO2 + CaO -> CaCO3 реакция соединения
N2O5 + H2O -> 2HNO3 реакция соединения
Na2CO3 + Ca(NO3)2 -> CaCO3 + 2NaNO3 реакция обмена
4P + 5O2 -> 2P2O5 реакция соединения
CaCO3 + 2HCl -> CaCl2 + CO2 + H2O реакция обмена
H2SiO3 + 2KOH -> K2SiO3 + 2H2O реакция обмена
H3PO4 + 3AgNO3 -> Ag3PO4 +3 HNO3 реакция обмена
CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(+2) + SO4(-2) + 2Na(+) + 2OH(-) = Cu(OH)2 + 2Na(+) + SO4(-2)
Cu(+2) + 2OH(-) = Cu(OH)2
3KCl + Na3PO4 = K3PO4 + 3NaCl
3K(+) + 3Cl(-) + 3Na(+) + PO4(-3) = 3K(+) + PO4(-3) + 3Na(+) + 3Cl(-) ( реакция не идёт)
Al2(SO4)3 +3 BaCl2 =3 BaSO4 + 2AlCl3
2Al(+3) + 3SO4(-2) + 3Ba(+2) + 6Cl(-) = 3BaSO4 + 2Al(+3) + 6Cl(-)
3SO4(-2) + 3Ba(+2) = 3BaSO4
Na2SO3 + H2SO4 = Na2SO4 + SO2 + H2O
2Na(+) + SO3(-2) + 2H(+) + SO4(-2) = 2Na(+) + SO4(-2) + SO2 + H2O
SO3(-2) + 2H(+) = SO2 + H2O
Na2CO3 + H2SO4 = Na2SO4 + CO2 + H2O
2Na(+) + CO3(-2) + 2H(+) + SO4(-2) = 2Na(+) + SO4(-2) + CO2 + H2O
CO3(-2) + 2H(+) = CO2 + H2O
2NaOH + H2SO4 = Na2SO4 + 2H2O
2Na(+) + 2OH(-) + 2H(+) + SO4(-2) = 2Na(+) + SO4(-2) + 2H2O
2OH(-) + 2H(+) = 2H2O
CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(+2) + SO4(-2) + 2Na(+) + 2OH(-) = Cu(OH)2 + 2Na(+) + SO4(-2)
Cu(+2) + 2OH(-) = Cu(OH)2